Perubahan Sifat Kimia Tanah Entisols, Respons Agronomis, dan Produktivitas Padi setelah Lima Tahun Penerapan Sistem Organik dan Kimia di Wukirsari, Sleman, Yogyakarta - Yovi Avianto; Amir Noviyanto; Galang Indra Jaya; Alan Handru (Program Studi Agroteknologi INSTIPER, 2026)
Sustaining rice production while reducing soil degradation has become an important challenge in intensively cultivated paddy fields, particularly on Entisols that are highly responsive to management practices. This study evaluated changes in the chemical properties of Entisols and their implications for rice agronomic performance after five years of organic and chemical management in Wukirsari, Sleman, Yogyakarta. Soil samples were collected from paddy fields under organic and chemical systems and analyzed for pH, C-organic, organic matter, cation exchange capacity (CEC), total N, available P, exchangeable K, Ca, Mg, and total B. Agronomic parameters and grain yield were also observed. The organic system gradually improved major soil chemical properties, particularly pH, C-organic, organic matter, available P, exchangeable Ca, and Mg. Relative change analysis showed that the strongest positive responses under organic management occurred in organic matter, available P, exchangeable K, Mg, and total B after five years. These improvements were followed by better root dry weight density, root length, and productive tiller number. Rice productivity under organic management increased from 5.2 t ha⁻¹ in the first year to 7.5 t ha⁻¹ in the fifth year, which was not significantly different from the chemical system (7.8 t ha⁻¹). These findings indicate that long-term organic management can progressively improve soil fertility and maintain rice productivity, implying that organic-based management is a promising strategy for sustaining paddy production while enhancing soil quality in Entisol-dominated agricultural areas.